Aging and the perception of texture-defined form. (October 2021) - Norman, J. Farley; Shapiro, Hannah K.; Sanders, Karli N.; Sher, Abdallah F.
Abstract: In this study 28 younger and older observers discriminated the global shapes of objects that were defined by differences in texture. The judged stimulus patterns were 3-point micropattern textures. On any given trial, a texture-defined shape (either a vertically- or horizontally-oriented rectangle) was presented; the observers' task was to discriminate between the two rectangles. The task difficulty was manipulated by varying the deviation from colinearity of each of the individual 3-point texture elements between figure and background (the larger the difference in deviation between figure and ground, the higher the discrimination performance). The results revealed a substantial effect of age. In order for the older observers to reliably discriminate the shape of the target rectangle (with a d' value of 1.5), they needed differences from colinearity that were 54.4 percent larger than those required for the younger observers. While older adults can utilize differences in texture to perceive global shape, their ability is nevertheless significantly impaired.